Unique Existence Theorem of Solution of Almost Periodic Differential Equations on Time Scales - Meng Hu; Lili Wang (Discrete Dynamics in Nature and Society)
By using the theory of calculus on time scales and M-matrix theory, the unique existence theorem of solution of almost periodic differential equations on almost periodic time scales is established. The result can be used to a large of dynamic systems.